Sebaceous nevus syndrome as the underlying cause of intractable seizures in a one-month-old infant - Anannit Visudtibhan (2018)
A one-month-old male infant with generalized seizures since 2 days old was evaluated at the Department of Pediatrics, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, Thailand. His seizures were initially characterized as focal movement of the right upper and lower limbs followed by generalized tonic. Initially, phenobarbital was administered but failed to control his seizures. Physical examination revealed generalized mild hypotonia with a hyperpigmented brownish patch affecting the left side of his face. The initial diagnosis was sebaceous nevus syndrome which is one of the neurocutaneous syndromes. The diagnosis was confirmed by skin biopsy of the affected lesion. The literature was reviewed and discussed. The authors emphasized the importance of thorough physical examination including evaluation of specific skin lesion which would be a leading clue in making the diagnosis of symptomatic epilepsy in infants.